1996
DOI: 10.5935/0305-7518.19960033
|View full text |Cite
|
Sign up to set email alerts
|

Squamous cell carcinoma of the foot arising in chronic ulcers in leprosy patients

Abstract: Summary Squamous cell carcinoma (SeC) of the foot is a rare sequelae of chronic ulceration secondary to leprosy neuropathy. Most of the tumours are relatively slow growing and tend to metastasize late. Survival after local excision is generally good. In this series of 17 patients so far there have been 3 deaths attributable to see, all of whom presented with locally advanced tumours and lymph node metastasis.Leprosy is a chronic infectious disease caused by My cobacterium leprae which pre dominantly affects sk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
21
0
4

Year Published

2000
2000
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(26 citation statements)
references
References 0 publications
0
21
0
4
Order By: Relevance
“…Chronic ulcers, usually on the feet, 9 are the most common complication in patients with leprosy presenting with chronic peripheral neuropathy (neuropathic ulcers) 6,8,9 . Neoplastic transformation of ulcers was thought to be rare, 8 but recent epidemiologic studies have shown that malignant transformation of chronic ulcers in patients with leprosy is more common than previously believed 9,10 . The first report of malignant transformation of chronic ulcers in patients with leprosy was described in 1942 10 .…”
mentioning
confidence: 99%
“…Chronic ulcers, usually on the feet, 9 are the most common complication in patients with leprosy presenting with chronic peripheral neuropathy (neuropathic ulcers) 6,8,9 . Neoplastic transformation of ulcers was thought to be rare, 8 but recent epidemiologic studies have shown that malignant transformation of chronic ulcers in patients with leprosy is more common than previously believed 9,10 . The first report of malignant transformation of chronic ulcers in patients with leprosy was described in 1942 10 .…”
mentioning
confidence: 99%
“…Recent epidemiological studies proved this complication was not as rare as it has been considered in the past. 1,2 We present two leprosy patients who developed squamous cell carcinoma (SCC) in chronic trophic ulcers. This is the first report from Greece.…”
mentioning
confidence: 99%
“… 3–7 A variety of predisposing factors are mentioned, such as long duration of the ulcer, constant irritation and traumatization, chronic infection with or without osteomyelitis, poor hygiene, environmental factors, genetic factors, repeated cytodestructive treatments such as cryotherapy and curettage. 1,2,4 Men 60–69 years of age suffering for 30–35 years of BT or BL are most likely to develop malignancy. Nerve damage is quite severe in BT or BL; which explains why patients with this type of leprosy are at high risk.…”
mentioning
confidence: 99%
See 2 more Smart Citations